Exploring the association of dairy product intake with the fatty acids C15:0 and C17:0 measured from dried blood spots in a multipopulation cohort: Findings from the Food4Me study. Issue 4 (28th January 2016) - Albani, Viviana; Celis‐Morales, Carlos; Marsaux, Cyril F. M.; Forster, Hannah; O'Donovan, Clare B.; Woolhead, Clara; Macready, Anna L.; Fallaize, Rosalind; Navas‐Carretero, Santiago; San‐Cristobal, Rodrigo; Kolossa, Silvia; Mavrogianni, Christina; et al.
Abstract : The study explored the association between C15:0 and C17:0 levels in dried‐blood spots and intake of dairy, including high‐fat and low‐fat dairy products. Abstract : Scope: The use of biomarkers in the objective assessment of dietary intake is a high priority in nutrition research. The aim of this study was to examine pentadecanoic acid (C15:0) and heptadecanoic acid (C17:0) as biomarkers of dairy foods intake. Methods and results: The data used in the present study were obtained as part of the Food4me Study. Estimates of C15:0 and C17:0 from dried blood spots and intakes of dairy from a Food Frequency Questionnaire were obtained from participants ( n = 1180) across seven countries. Regression analyses were used to explore associations of biomarkers with dairy intake levels and receiver operating characteristic analyses were used to evaluate the fatty acids. Significant positive associations were found between C15:0 and total intakes of high‐fat dairy products. C15:0 showed good ability to distinguish between low and high consumers of high‐fat dairy products. Conclusion: C15:0 can be used as a biomarker of high‐fat dairy intake and of specific high‐fat dairy products. Both C15:0 and C17:0 performed poorly for total dairy intake highlighting the need for caution when using these in epidemiological studies.